Pengaruh Work From Home (WFH) terhadap Kepuasan Kerja dan Disiplin Kerja yang Berdampak pada Kinerja Karyawan PT Jimmulya - Monica Mandasari; Asmanita Asmanita (Universitas Batanghari, 2022)
This study aims to determine the effect of work from home on job satisfaction and work discipline that has an impact on employee performance at PT Jimmulya. Respondents in this study amounted to 60 people, while the data analysis tool used in this study used quantitative analysis methods. The data were collected through questionnaires and observation. The measurement scale of the variables in this study refers to the Likert scale. starting point for constructing a statement or question. The data analysis tool in this thesis uses simple linear regression analysis using the SPSS program to calculate the magnitude of the effect of Y on the X variable where the regression results show tcount 6,955 & 6,891 with a significance of 0.000 < 0.5. The significance value is less than 0.5, so Ho is rejected and Ha is accepted. So it can be concluded that there is a partially significant effect between Work From Home on Job Satisfaction and Work Discipline of PT Jimmulya Employees.